The fire next time - Baldwin, James, 1924-1987. (New York : Vintage International, 1993)
Contains a letter to Baldwin's nephew on the 100th anniversary of the Emancipation Proclamation describing his childhood, views on Black Muslims, and his visions.
Booklist.
Wilson's Senior High School.
Booklist, August 1997.
Wilson's Senior High School, November 1997.
Young Adult.
Young Adult
Keywords: African Americans; Black Muslims; African Americans; Black Muslims; United States -- Race relations; United States -- Race relations